Penggunaan Fitur Shopee PayLater Dalam Perspektif Ekonomi Islam Dikalangan Mahasiswa Universitas Halim Sanusi Prodi Ekonomi Islam - Nurrahman, Ahmad Gemma; Miptahudin, Iip (Jurnal Hukum Ekonomi Syariah, 2025)
This study aims to analyze the use of the Shopee PayLater feature in the perspective of Islamic economics among students of the Islamic Economics Study Program at Halim Sanusi University. The research method used is a qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study show that the majority of students use Shopee PayLater for consumptive needs, such as purchasing non-priority goods. From an Islamic economic perspective, this practice contains several elements that need to be reviewed, such as the potential for usury, gharar and consumerism that are not in accordance with the principles of maqashid sharia. In conclusion, more intensive sharia financial education is needed for students so that they are able to assess digital financial products wisely and in accordance with sharia principles.  Keywords: Shopee PayLater, Islamic Economics, Students